The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7554/elife.60607
|View full text |Cite
|
Sign up to set email alerts
|

BipA exerts temperature-dependent translational control of biofilm-associated colony morphology in Vibrio cholerae

Abstract: Adaptation to shifting temperatures is crucial for the survival of the bacterial pathogen Vibrio cholerae. Here, we show that colony rugosity, a biofilm-associated phenotype, is regulated by temperature in V. cholerae strains that naturally lack the master biofilm transcriptional regulator HapR. Using transposon-insertion mutagenesis, we found the V. cholerae ortholog of BipA, a conserved ribosome-associated GTPase, is critical for this temperature-dependent phenomenon. Proteomic analyses revealed that loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Other extracellular proteins have been identified in our proteomic analysis. Among them, Bap1, Crr and BipA have a role in biofilm formation and regulation (Absalon et al ., 2011; Del Peso Santos et al ., 2021), and GbpA and CpbD are involved in adhesion and aggregation respectively (Wong et al ., 2012; Jemielita et al ., 2018). The haemolysin Lec and the Hcp are both more abundant in the presence of PmB.…”
Section: Resultsmentioning
confidence: 99%
“…Other extracellular proteins have been identified in our proteomic analysis. Among them, Bap1, Crr and BipA have a role in biofilm formation and regulation (Absalon et al ., 2011; Del Peso Santos et al ., 2021), and GbpA and CpbD are involved in adhesion and aggregation respectively (Wong et al ., 2012; Jemielita et al ., 2018). The haemolysin Lec and the Hcp are both more abundant in the presence of PmB.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, recent quantitative mass spectrometry data nicely showed the accumulated pre-50S intermediates in bipA mutant cells at suboptimal temperature, with several r-proteins absent, further demonstrating the role of BipA in 50S subunit assembly ( Gibbs et al, 2020 ). Furthermore, a paper published during our manuscript preparation revealed that bacteria can remodel their protein expression relevant to biofilm formation in a temperature-dependent manner by modulating BipA abundance ( Del Peso Santos et al, 2021 ). With the desire to support the ongoing effort in BipA-related studies and to expand our efforts on structural study of ribosome-associated proteins and biofilm formation as well as its relevant pathogenesis and resistance ( Tanaka et al, 2008 ; Selmer et al, 2012 ; Kumar et al, 2015 ; Yu et al, 2015 ; Ero et al, 2016 ; Kumar et al, 2016 ; Yang et al, 2017 ), here we report additional evidence to demonstrate the role of BipA in ribosome biogenesis, specifically in large subunit 50S maturation, and conditional protein translation at suboptimal temperature through combinative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the deletion of bipA hampers biofilm formation in E. coli , as well as in bacteria such as Bordetella holmesii , Pseudomonas aeruginosa , and Vibrio cholerae ( Neidig et al, 2013 ; Hiramatsu et al, 2016 ; Del Peso Santos et al, 2021 ). The overproduced colanic acid capsule shields bacterial surface adhesins and antagonizes the attachment stage during biofilm development ( Schembri et al, 2004 ).…”
Section: Resultsmentioning
confidence: 96%